Effect of Graphene Addition on Bacterial Cellulose-Based Nanocomposite - Maulana, Jibril; Suryanto, Heru; Aminnudin, Aminnudin (Journal of Mechanical Engineering Science and Technology (JMEST), 2022)
Bacterial cellulose (BC) is a widespread, low-cost biopolymer that has generally been produced from plants and biomass waste. A method for improving the range of applications for bacterial cellulose is adding graphene material. It has an outstanding feature that can increase the performance of nanocomposite materials. The research aims to observe the effect of graphene on the surface morphology, crystallinity, chemical bonding, and tensile strength of BC/CuO nanocomposite. For this study's synthesis, BC was synthesized by fermenting pineapple peel extract for 10 to 14 days. The produced BC was crushed, homogenized with a nano homogenizer machine, and filtered. Filtered BC, CuO, and graphene were added to obtain a solution, and the mixture was first stirred magnetically, followed by an ultrasonic homogenizer, and finally dried using a freeze-dry method to make a porous nanocomposite. According to SEM analysis, the addition of CuO and graphene can fill porosity nanocomposite. By XRD analysis, the addition of graphene reduces the crystallinity of BC/CuO. The FTIR data showed that adding graphene reduces hydrogen bonding and makes some Cu-O-C bonding. The tensile test has demonstrated that the tensile strength of BC-based nanocomposite with graphene reinforcement tends to decrease.